LITERATURE REVIEW: PENGARUH SISTEM ARSIP DIGITAL TERHADAP MUTU PELAYANAN ADMINISTRATIF DI MADRASAH DAN PESANTREN - Ma'rifah, Imroatul (STKIP Pesisir Selatan, 2025)
This study aims to analyze the impact of digital archive systems on administrative service quality in madrasah and pesantren, identifying affected service dimensions, implementation success factors, adoption challenges, and best practices for system optimization. A systematic literature review was conducted on 2020-2025 publications through Google Scholar, ERIC, Scopus, and Portal Garuda databases. From 411 identified articles, 14 high-quality studies were analyzed using thematic narrative synthesis after screening, eligibility evaluation, and methodological assessment stages.: Archive digitalization enhances five service quality dimensions: service speed, data accuracy, information accessibility, management transparency, and document security. Success is determined by leadership commitment, human resource competence, technological infrastructure, and policy support. Major challenges include limited human resources, inadequate infrastructure, resistance to change, and intergenerational digital divide. This research fills the literature gap by integrating theoretical-empirical perspectives specific to madrasah-pesantren contexts, demonstrating that administrative modernization can proceed synergistically without sacrificing traditional values, and formulating evidence-based strategic recommendations for digitalization policy development in Islamic educational institutions.